2011
DOI: 10.1074/jbc.m111.278184
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-localized Antisense Small RNAs with 5′-Polyphosphate Termini Regulate Long Term Transcriptional Gene Silencing in Entamoeba histolytica G3 Strain

Abstract: Background: The mechanism(s) of G3-based TGS in E. histolytica is largely unknown. Results: 5Ј-polyphosphate antisense sRNAs are identified; mechanistic insights linking these sRNAs with TGS are provided by IFA, FISH, IP, and ChIP assays. Conclusion: TGS in E. histolytica G3 strain is mediated by an siRNA pathway, which utilizes antisense 5Ј-polyphosphate sRNAs. Significance: This is the first demonstration of (a) 5Ј-polyphosphate antisense sRNAs mediating TGS and (b) RNAi-mediated TGS in protozoan parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 47 publications
4
74
0
Order By: Relevance
“…Previously, using a commercial ␣-H3 antibody we and others have demonstrated increased occupancy of H3 at loci affected by small RNA (sRNA)-mediated gene silencing in the E. histolytica G3 strain (33,37). To more specifically investigate the mechanism of small RNA-induced transcriptional gene silencing, we asked if post-translationally modified H3 histone (H3K27Me2) contributes to small RNA gene silencing in E. histolytica.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, using a commercial ␣-H3 antibody we and others have demonstrated increased occupancy of H3 at loci affected by small RNA (sRNA)-mediated gene silencing in the E. histolytica G3 strain (33,37). To more specifically investigate the mechanism of small RNA-induced transcriptional gene silencing, we asked if post-translationally modified H3 histone (H3K27Me2) contributes to small RNA gene silencing in E. histolytica.…”
Section: Resultsmentioning
confidence: 99%
“…Although many genes could be silenced using this approach, we also identified some genes that could not be silenced despite the generation of functional small RNAs (36). It has previously been demonstrated that RNAi-silenced loci have increased histone occupancy, however, given the sequence divergence of the amebic H3, commercially available reagents could not be applied to define the molecular modifications typically associated with heterochromatin (33,37).…”
mentioning
confidence: 92%
See 3 more Smart Citations